2013
DOI: 10.1089/scd.2012.0181
|View full text |Cite
|
Sign up to set email alerts
|

The Histone Methyltransferase Inhibitor BIX01294 Enhances the Cardiac Potential of Bone Marrow Cells

Abstract: Bone marrow (BM) has long been considered a potential stem cell source for cardiac repair due to its abundance and accessibility. Although previous investigations have generated cardiomyocytes from BM, yields have been low, and far less than produced from ES or induced pluripotent stem cells (iPSCs). Since differentiation of pluripotent cells is difficult to control, we investigated whether BM cardiac competency could be enhanced without making cells pluripotent. From screens of various molecules that have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 94 publications
2
37
0
Order By: Relevance
“…In this study, we investigated the role of G9a in neuroblastoma tumor growth together with BIX01294, which is a specific G9a inhibitor [32][34]. We provide experimental evidence supporting the role of G9a in the transcriptional regulation of autophagy in neuroblastoma cells.…”
Section: Introductionmentioning
confidence: 90%
“…In this study, we investigated the role of G9a in neuroblastoma tumor growth together with BIX01294, which is a specific G9a inhibitor [32][34]. We provide experimental evidence supporting the role of G9a in the transcriptional regulation of autophagy in neuroblastoma cells.…”
Section: Introductionmentioning
confidence: 90%
“…Inhibition of G9a activity with BIX01294 or siRNA significantly increased myogenic differentiation37. Bone marrow mesenchymal stem cells differentiated to cardiac-competent progenitors after BIX01294 treatment3839. Combination of small molecule inhibitors, BIX01294 and BayK8644 interfered with reprogramming of Oct4/Klf4-transduced mouse embryonic fibroblast into pluripotent stem cells40.…”
mentioning
confidence: 99%
“…In previous studies, we reported that BIX01294 can enhance the cardiac competency of bone marrow cells . As a follow‐up to that earlier finding, we wanted to investigate whether BIX01294 may also have a positive effect on progenitor cells within the heart.…”
Section: Resultsmentioning
confidence: 87%